(untitled) (Journal of Partial Differential Equations, 1995)
In this paper, we obtain the existence of positive solution of -Δu = b(x)(u - λ)^p_+,x ∈ R^N λ > 0, |∇ u| ∈ L² (R^N),u ∈ L2NN-2 (R^N) under the assumptions that 1 < p < N+2N-2, N ≥ 3, b(x) satisfies b(x) ∈ C(R^N), b(x) > 0 in R^N b(x) →_|x|→∞b^∞ and b(x) > 4p+3b^∞ for x ∈ R^N